Preliminary study to determine extent of linkage disequilibrium and estimates of autozygosity in Brazilian Gyr dairy cattle - Neves, H. H.R. [UNESP]; Desidério, J. A. [UNESP]; Pimentel, E. C.G.; Scalez, D. C.B. [UNESP]; Queiroz, S. A. [UNESP] (Cordoba University Press (UCOPress), 2015)
Genotypes of 25 artificial insemination sires were used to study the extent of linkage disequilibrium (LD) and the correspondence between pedigree and SNP-based estimators of inbreeding in Brazilian Gyr dairy cattle. Overall, 24,020 SNPs had minor allele frequencies (MAF) greater than 5 % and were used to calculate two measures of LD (r² and D’) for all pairs of markers in each autosome. LD was also used to estimate the effective population size (Ne) at different prior generations. Individual inbreeding coefficients (F) were estimated using either pedigree information (Fped, pedigree traced back up to 9 generations) or marker information. Marker-based estimates of F were derived based on the excess homozygosity (Fhet) in SNP markers and the estimated proportion of the genome located in runs of homozygosity (Froh). The mean LD between adjacent markers averaged across all autosomes was approximately 0.20 and 0.75, measured using r² and D’. Useful LD was identified between markers separated by up to 100 kb when screening this sample of Gyr dairy cattle. The effective population size showed a consistent trend of decay along time, falling below 56 in the last three generations. Weaker correspondence between individual inbreeding estimates based on runs of homozygosity and pedigree was verified in the present study (estimated correlations between Fped and Froh varied from 0.32 to 0.42). It appears to be feasible to apply genomic selection to Gyr cattle in Brazil, but further studies on the extent of linkage disequilibrium using a larger sample of this population are needed.
Estudo preliminar sobre a extensão do desequilíbrio de ligação e estimativas de autozigose em bovinos leiteiros da raça Gir
Keywords: Effective population size; Inbreeding; Pedigree; SNP